Identifying and Meeting the Needs of Extension’s Target Audiences - Laura A. Warner; Glenn D. Israel; John M. Diaz (EDIS)
This document provides an overview of the concept of target audiences as it relate to Extension education, and briefly presents concepts of audience analysis and educational content selection. In contrast to the general population, a target audience is comprised of people who can take some explicit action to help solve an identified problem addressed by an Extension program. Additionally, a target audience is sometimes the people who are affected most by that problem. An understanding of the concept of target audiences paired with intentional selection of appropriate educational activities and content can support an impactful Extension program.